Deciphering Voltage-gated Na(+) and Ca(2+) Channels By Studying Prokaryotic Ancestors - Catterall, William A. (Trends Biochem Sci, 2015)
Voltage-gated sodium (Na(V)) and calcium (Ca(V)) channels are involved in electrical signaling, contraction, secretion, synaptic transmission, and other physiological processes activated in response to depolarization. Despite their physiological importance, the structures of these closely related proteins have remained elusive because of their size and complexity. Bacterial Na(V) channels have structures analogous to a single domain of eukaryotic Na(V) and Ca(V) channels and are their likely evolutionary ancestor. In this article, we review recent work that has led to new understanding of Na(V) and Ca(V) channels through high-resolution structural studies of their prokaryotic ancestors. New insights into their voltage-dependent activation and inactivation, ion conductance, and ion selectivity provide realistic structural models for the function of these complex membrane proteins at the atomic level.